Calcium silicate nanosheet and stripping method thereof

By surface treatment and ultrasonic mixing on calcium silicate powder, calcium silicate gel is formed, and peeled through vacuum impregnation and ball milling, the problems of low peeling efficiency of calcium silicate nanosheets and damaged material properties in the prior art are solved. , high-performance calcium silicate nanosheets were obtained.

CN119219006AInactive Publication Date: 2024-12-31ZHEJIANG ASKER TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411762484.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when preparing calcium silicate nanosheets, mechanical peeling efficiency is low, chemical peeling requires a large amount of chemical reagent and complexity, intercalation peeling requires a large amount of intercalation agent, which affects the surface properties of the material.

Method used

Calcium silicate powder is stirred in a silicon-containing coupling agent and separated and dried to obtain activated calcium silicate. It is then mixed with ethyl orthosilicate and calcium ion solution to form a calcium silicate gel, and is impregnated by vacuum and Ball mill peeling to obtain modified calcium silicate nanosheets.

Benefits of technology

The peeling efficiency and purity of calcium silicate nanosheets are improved, the high mechanical properties, thermal stability and biocompatibility of the material are maintained, while reducing the amount of chemical reagents used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a calcium silicate nanosheet and a stripping method thereof, and relates to the technical field of calcium silicate materials. The stripping method provided by the invention comprises the following steps: stirring and mixing calcium silicate powder in a silicon-containing coupling agent, separating and drying to obtain activated calcium silicate; performing ultrasonic mixing on the activated calcium silicate and tetraethoxysilane to prepare a mixed suspension; performing ultrasonic mixing on the mixed suspension and a calcium ion solution, and separating to obtain calcium silicate gel; the calcium silicate gel and the xonotlite product are subjected to vacuum impregnation and then aged, and modified calcium silicate is prepared; and carrying out ball milling and stripping on the modified calcium silicate to obtain the calcium silicate nanosheet. According to the stripping method provided by the invention, calcium silicate is gelatinized and then subjected to ball-milling separation to obtain the nanosheets, so that the high-quality calcium silicate nanosheets can be quickly and conveniently obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium silicate materials, and in particular to a calcium silicate nanosheet and a peeling method thereof. Background Art

[0002] Calcium silicate is a new type of nanomaterial, usually with a layered structure, composed of alternating silicon-oxygen tetrahedrons and calcium-oxygen octahedrons. This layered structure gives calcium silicate nanosheets a high specific surface area, good thermal stability and chemical stability. Due to its unique structure, calcium silicate nanosheets are widely used in nanocomposites, biomedicine, and energy storage.

[0003] In the prior art, mechanical exfoliation, chemical exfoliation and intercalation exfoliation are usually used to prepare calcium silicate nanosheets. The mechanical exfoliation method mainly uses mechanical shear force to exfoliate the calcium silicate nanosheets from the bulk material, while the chemical exfoliation method exfoliates the nanosheets by chemical methods. The intercalation exfoliation method mainly inserts an intercalating agent between the calcium silicate nanosheets, increases the interlayer spacing between adjacent calcium silicate nanosheets, and uses mechanical or chemical forces to exfoliate.

[0004] However, the mechanical stripping method has a low stripping efficiency and requires sufficient mechanical force to complete the stripping of a certain amount of nanosheets. The chemical stripping method requires the use of more chemical reagents, and the post-processing process is more complicated and easily destroys the structure of the calcium silicate nanosheets themselves. The intercalation stripping method requires the use of a large amount of intercalating agents, which will directly change the surface properties of the calcium silicate nanosheets. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a calcium silicate nanosheet and a peeling method thereof.

[0006] In a first aspect, the present invention provides a method for exfoliating calcium silicate nanosheets, comprising the following steps: stirring and mixing calcium silicate powder in a silicon-containing coupling agent, separating and drying to obtain activated calcium silicate; ultrasonically mixing the activated calcium silicate with ethyl orthosilicate to obtain a mixed suspension; ultrasonically mixing the mixed suspension with a calcium ion solution, and separating to obtain a calcium silicate gel; vacuum impregnating the calcium silicate gel with a xonotlite product, and then aging to obtain modified calcium silicate; and ball-milling and exfoliating the modified calcium silicate to obtain calcium silicate nanosheets.

[0007] Optionally, when the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the average particle size of the calcium silicate powder is 1-5 μm.

[0008] Optionally, when the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the volume density of the calcium silicate powder is 0.2-0.5 g / m 3 .

[0009] Optionally, when the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent, the mass ratio of the calcium silicate powder to the silicon-containing coupling agent is 1:(0.1-0.2).

[0010] Optionally, when the calcium silicate powder is stirred and mixed in a silicon-containing coupling agent, the silicon-containing coupling agent includes one of γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, phenyltriethoxysilane and dodecyltrimethoxysilane.

[0011] Optionally, when the activated calcium silicate is obtained by separation and drying: after vacuum filtration, the activated calcium silicate is obtained by drying.

[0012] Optionally, when the activated calcium silicate is obtained by separation and drying: after separation, the activated calcium silicate is dried at 50-70°C to obtain the activated calcium silicate.

[0013] Optionally, when the activated calcium silicate is obtained by separation and drying: the activated calcium silicate is obtained by drying under a vacuum environment after separation.

[0014] Optionally, when the activated calcium silicate is obtained by separation and drying: after separation, the activated calcium silicate is rinsed with a solution containing a silicon-containing coupling agent and then dried to obtain the activated calcium silicate.

[0015] Optionally, when the activated calcium silicate is obtained by separation and drying: after separation, the activated calcium silicate is washed by centrifugation at 100-200 rpm using deionized water, and then dried to obtain the activated calcium silicate.

[0016] Optionally, when the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed to prepare a mixed suspension, the mass ratio of the activated calcium silicate to ethyl orthosilicate is 1:(5-10).

[0017] Optionally, when the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed to obtain a mixed suspension: the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed at a frequency of 10-30 kHz.

[0018] Optionally, when the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed to obtain a mixed suspension: the mixed suspension is mixed with anhydrous ethanol and then adjusted to a solid content of the activated calcium silicate of 0.1-0.12 g / mL.

[0019] Optionally, when the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed to obtain a mixed suspension: the activated calcium silicate is preheated at 40-50° C. and then ultrasonically mixed with ethyl orthosilicate.

[0020] Optionally, when the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed to obtain a mixed suspension: the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed at 40-50° C. to obtain a mixed suspension.

[0021] Optionally, when the mixed suspension is ultrasonically mixed with the calcium ion solution: the calcium ion solute in the calcium ion solution includes one of calcium chloride, calcium nitrate and calcium acetate.

[0022] Optionally, when the mixed suspension is ultrasonically mixed with the calcium ion solution: the calcium ion solution is added dropwise into the mixed suspension under ultrasound to mix.

[0023] Optionally, when the mixed suspension is ultrasonically mixed with the calcium ion solution, the mass ratio of activated calcium silicate in the mixed suspension to calcium ions in the calcium ion solution is 1:(0.02-0.04).

[0024] Optionally, when the mixed suspension is ultrasonically mixed with the calcium ion solution: the solvent of the calcium ion solution includes deionized water.

[0025] Optionally, when ultrasonically mixing the mixed suspension with the calcium ion solution: ultrasonically mixing the mixed suspension with the calcium ion solution at 40-50°C.

[0026] Optionally, when ultrasonically mixing the mixed suspension with the calcium ion solution: the mixed suspension and the calcium ion solution are ultrasonically mixed at a frequency of 10-30 kHz.

[0027] Optionally, when the calcium silicate gel and the xonotlite product are vacuum impregnated, the mass ratio of the calcium silicate gel to the xonotlite product is 1:(0.3-0.5).

[0028] Optionally, when the calcium silicate gel and the xonotlite product are vacuum impregnated: the calcium silicate gel and the xonotlite product are impregnated in a vacuum environment for 2-4 hours.

[0029] Optionally, when the calcium silicate gel and the xonotlite product are vacuum impregnated: the xonotlite product is prepared from a calcium-containing raw material and a silicon-containing raw material in an alkaline environment.

[0030] Optionally, when the calcium silicate gel and the xonotlite product are vacuum impregnated: the xonotlite product is immersed in the calcium silicate gel in a vacuum environment.

[0031] Optionally, when the modified calcium silicate is obtained by aging after vacuum impregnation: the modified calcium silicate is obtained by immersing the solution in an ethanol aqueous solution with an ethanol volume fraction of 10-30% for 24-48 hours for aging.

[0032] Optionally, when the modified calcium silicate is obtained by aging after vacuum impregnation: the modified calcium silicate is obtained by aging under a pressure of 2-3 atm.

[0033] Optionally, when the modified calcium silicate is obtained by aging after vacuum impregnation: the modified calcium silicate is obtained by vacuum drying.

[0034] Optionally, when the modified calcium silicate is subjected to ball milling and exfoliation to obtain calcium silicate nanosheets, the modified calcium silicate is subjected to ball milling and exfoliation at a ball-to-material ratio of (15-25):1 and a rotation speed of 100-200 rpm for 10-12 hours to obtain the calcium silicate nanosheets.

[0035] Optionally, when the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the silicon-containing coupling agent is dissolved in advance to prepare a coupling solution, and then the calcium silicate powder is ultrasonically mixed in the coupling solution.

[0036] Optionally, when the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the calcium silicate powder is kept warm in a vacuum environment at 50-55° C. for pre-activation.

[0037] Optionally, when the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the calcium silicate powder and the silicon-containing coupling agent are stirred and mixed at 50-55°C.

[0038] In a second aspect, the present invention also provides a calcium silicate nanosheet obtained by exfoliation using any of the above optional exfoliation methods. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0040] The present invention provides a method for peeling calcium silicate nanosheets, comprising the following steps: S1, stirring and mixing calcium silicate powder in a silicon-containing coupling agent, separating and drying to obtain activated calcium silicate; S2, ultrasonically mixing activated calcium silicate and ethyl orthosilicate to prepare a mixed suspension; S3, ultrasonically mixing the mixed suspension and the calcium ion solution and separating them to obtain calcium silicate gel; S4, vacuum impregnating the calcium silicate gel and the xonotlite product and then aging them to obtain modified calcium silicate; S5. Ball milling and exfoliation of the modified calcium silicate to obtain calcium silicate nanosheets.

[0041] In fact, after the surface treatment of the calcium silicate powder with the silicon-containing coupling agent in step S1, the silicon-containing coupling agent can form active groups on the surface of the calcium silicate powder, thereby facilitating the improvement of the surface active sites and reaction activity of the calcium silicate powder. In addition, the silicon-containing groups connected to the surface of the calcium silicate powder can provide connection points for the connection of ethyl orthosilicate in step S2, thereby facilitating the progress of step S2.

[0042] In fact, ultrasonically mixing the activated calcium silicate and ethyl orthosilicate in step S2 can promote the full dispersion of the activated calcium silicate and ethyl orthosilicate, thereby promoting the uniform distribution of ethyl orthosilicate on the surface of the activated calcium silicate. In addition, ethyl orthosilicate can undergo hydrolysis to generate silicic acid, and silicic acid can react with the calcium ions added in step S3 to generate nano-calcium silicate, thereby modifying the defects and structure of the surface of the activated calcium silicate.

[0043] In fact, after the mixed suspension is ultrasonically mixed with the calcium ion solution in step S3, the calcium ions can react with the silicate ions produced by hydrolysis in the mixed suspension to generate calcium silicate, which can not only modify the surface of the activated calcium silicate, but also form a gel material, and use the activated calcium silicate as a skeleton structure to form a calcium silicate gel, and the purity of the calcium silicate gel can be improved after separation.

[0044] In fact, when the calcium silicate gel and the xonotlite product are vacuum impregnated in step S4, it is beneficial for the calcium silicate gel to fully penetrate into the pores of the xonotlite product, and the structure of the xonotlite product can help the surface morphology and structure after the calcium silicate infiltrates, which is beneficial to the peeling of high-performance calcium silicate nanosheets.

[0045] In fact, by using ball milling to destroy the block structure of calcium silicate in step S5, the modified calcium silicate undergoes physical changes through mechanical force, overcoming the internal binding force, thereby completing the separation of the layered structure, and obtaining calcium silicate nanosheets with a large specific surface area, high mechanical properties, thermal stability and biocompatibility.

[0046] In some embodiments, when executing step S1, the average particle size of the calcium silicate powder used is 1-5 μm. In fact, the calcium silicate powder can be a conventional commercial product, or it can be synthesized in a laboratory or factory using conventional synthesis methods. In fact, the use of micron-grade calcium silicate powder is conducive to surface treatment of calcium silicate nanosheets and forming a uniform calcium silicate gel. Specifically, the volume density of the calcium silicate powder used is 0.2-0.5 g / m 3 .

[0047] In some embodiments, when performing step S1, the mass ratio of calcium silicate powder to silicon-containing coupling agent is 1:(0.1-0.2). This is conducive to the silicon-containing coupling agent to fully contact the surface of the calcium silicate powder, thereby improving the surface modification effect of the silicon-containing coupling agent on the calcium silicate powder. Specifically, the silicon-containing coupling agent includes one of γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, phenyltriethoxysilane and dodecyltrimethoxysilane.

[0048] In fact, when executing step S1, the silicon-containing coupling agent can be dissolved in advance to prepare a coupling solution, and then the calcium silicate powder can be ultrasonically mixed in the coupling solution. Specifically, when the silicon-containing coupling agent is a liquid at room temperature, anhydrous ethanol, ether and other common reagents can be added to the silane coupling agent for dilution before use; when the silicon-containing coupling agent is a solid at room temperature, it can be dissolved in anhydrous ethanol, ether and other common reagents for use.

[0049] In some embodiments, when executing step S1, the calcium silicate powder is kept in a vacuum environment at 50-55°C for preheating activation, and then the silicon-containing coupling agent is kept in a water bath environment at 50-55°C for 20-30 minutes, and then the preheated activated calcium silicate powder is added to the silicon-containing coupling agent for ultrasonic mixing. In fact, preheating and activating the calcium silicate powder is beneficial to improving the activity of the calcium silicate powder when the silicon-containing coupling agent is used for surface treatment.

[0050] Specifically, after executing step S1, by surface treating the calcium silicate powder with a silicon-containing coupling agent, not only can silicon-containing active groups be introduced on the surface of the calcium silicate powder, but also the dispersibility of the calcium silicate powder can be improved, thereby avoiding agglomeration of the calcium silicate powder.

[0051] In some embodiments, when performing separation and drying in step S1, vacuum filtration may be performed. In fact, separation means commonly used in the art may be used during separation and drying to achieve solid-liquid separation, and specifically, filtration separation, centrifugal separation, etc. In fact, by separating the surface-treated calcium silicate powder from the silicon-containing coupling agent, it is beneficial to control the degree of modification of the surface of the calcium silicate powder by the silicon-containing coupling agent.

[0052] In some embodiments, after performing step S1 to separate the surface-treated calcium silicate powder, the obtained calcium silicate powder is dried in a vacuum environment at 50-70° C. Specifically, it can be dried in a vacuum environment at 50-70° C. to constant weight to obtain activated calcium silicate with stable properties.

[0053] In some embodiments, after performing solid-liquid separation on the surface-treated calcium silicate powder in step S1, the surface-treated calcium silicate powder may be rinsed with a solution containing a silicon-containing coupling agent. In fact, the residual liquid containing the silicon-containing coupling agent obtained after separation from the surface-treated calcium silicate powder may be used for rinsing, which can further improve the uniformity of the surface treatment of the calcium silicate powder by the silicon-containing coupling agent.

[0054] In some embodiments, after performing solid-liquid separation on the surface-treated calcium silicate powder in step S1, the obtained solid can be mixed with deionized water, and the obtained mixed liquid can be centrifuged and washed at a speed of 100-200 rpm, which is conducive to fully mixing the silicon-containing coupling agent attached to the surface of the calcium silicate powder and removing excess silicon-containing coupling agent.

[0055] In some embodiments, when executing step S2 to ultrasonically mix the activated calcium silicate and the ethyl orthosilicate to obtain a mixed suspension, the mass ratio of the activated calcium silicate used to the ethyl orthosilicate used is 1:(5-10), which is conducive to the uniform contact of the ethyl orthosilicate with the surface of the activated calcium silicate, and then the ethyl orthosilicate is connected using the silicon-containing active groups attached to the surface of the activated calcium silicate, and the surface of the activated calcium silicate is defect-modified.

[0056] In some embodiments, when executing step S2, the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed at a frequency of 10-30 kHz. In this way, the ultrasonic cavitation effect can be used to further inhibit the agglomeration of the activated calcium silicate in the ethyl orthosilicate, and at the same time, tiny bubbles attached to the surface of the activated calcium silicate can be removed, thereby improving the contact ability of ethyl orthosilicate with the surface of the activated calcium silicate.

[0057] In some embodiments, when performing step S2, when the activated calcium silicate and ethyl orthosilicate are mixed to obtain a mixed suspension, in order to reduce the viscosity of ethyl orthosilicate and improve the contact efficiency between ethyl orthosilicate and activated calcium silicate, the mixed suspension can be stirred and mixed with anhydrous ethanol, and the amount of anhydrous ethanol added is such that the solid content of the activated calcium silicate is 0.1-0.12 g / mL. In this way, the addition of anhydrous ethanol can not only inhibit the hydrolysis of ethyl orthosilicate during the attachment process of ethyl orthosilicate, but also improve the contact efficiency between ethyl orthosilicate and the surface of activated calcium silicate.

[0058] In some embodiments, when executing step S2, the activated calcium silicate can be preheated in a vacuum environment at 40-50°C for 1-2 hours to increase the activity of the surface groups of the activated calcium silicate and avoid surface denaturation of the activated calcium silicate due to excessively high temperature. In addition, the ethyl orthosilicate can be preheated in a water bath environment at 40-50°C for 0.5-1 hour, and then the preheated activated calcium silicate is added to the ethyl orthosilicate and ultrasonically mixed in a water bath environment at 40-50°C.

[0059] In some embodiments, when the mixed suspension is ultrasonically mixed with the calcium ion solution in step S3, the calcium ion solute in the calcium ion solution used includes one of calcium chloride, calcium nitrate, and calcium acetate, and the solvent of the calcium ion solution includes deionized water. In fact, the calcium ion solution used can be a saturated solution. In addition, after the mixed suspension is mixed with the calcium ion solution, the water in the calcium ion solution can not only promote the hydrolysis of ethyl orthosilicate in the mixed suspension, thereby forming silicic acid and forming calcium silicate with calcium ions on the surface of activated calcium silicate for defect modification, but also form a gel structure.

[0060] In some embodiments, when the mixed suspension and the calcium ion solution are ultrasonically mixed in step S3, the mass ratio of the activated calcium silicate in the mixed suspension to the calcium ions in the calcium ion solution is 1:(0.02-0.04), which can regulate the morphology and quality of the calcium silicate formed on the surface of the activated calcium silicate, and is beneficial to regulating the structure of the generated calcium silicate gel.

[0061] In some embodiments, when executing step S3, during the process of ultrasonically mixing the mixed suspension, the calcium ion solution is added dropwise into the mixed suspension, so that the calcium ion concentration in the mixed suspension gradually increases, and it is beneficial to adjust the formation of calcium silicate gel in the mixed suspension, so that the calcium ions are preliminarily combined with the silicate on the surface of the activated calcium silicate to form calcium silicate, and then gel formation is performed. Specifically, the total time of adding the calcium ion solution is controlled to be 30-60 minutes.

[0062] In some embodiments, when executing step S3, the mixed suspension and the calcium ion solution are ultrasonically mixed in a water bath environment at 40-50° C., and the external temperature is controlled to promote the hydrolysis of ethyl orthosilicate and increase the combination of silicic acid and calcium ions to form calcium silicate. At the same time, the formation of calcium silicate gel can be delayed, so that the defects on the surface of the activated calcium silicate can be further modified. Specifically, the mixed suspension and the calcium ion solution are ultrasonically mixed at a frequency of 10-30 kHz.

[0063] In some embodiments, when the calcium silicate gel and the xonotlite product are vacuum impregnated in step S4, the mass ratio of the calcium silicate gel to the xonotlite product is 1:(0.3-0.5). In fact, by adjusting the mass ratio of the calcium silicate gel to the xonotlite product, it is beneficial to absorb more calcium silicate gel in a unit xonotlite product, thereby adjusting the structure of the calcium silicate nanosheets obtained after peeling.

[0064] In some embodiments, when performing step S4, the calcium silicate gel and the xonotlite product are immersed in a vacuum environment for 2-4 hours. In fact, the air pressure of the immersion environment of the calcium silicate gel and the xonotlite product is less than or equal to 100 Pa, and the xonotlite product is completely immersed in the calcium silicate gel, which is conducive to the infiltration of the calcium silicate gel into the pores inside the xonotlite product.

[0065] In some embodiments, when executing step S4, the xonotlite product used is prepared from a calcium-containing raw material and a silicon-containing raw material in an alkaline environment. Specifically, the preparation method of the xonotlite product includes: mixing calcium hydroxide, silicon dioxide, and potassium hydroxide in a mass ratio of (8-10): (8-10): (0.1-0.2), putting them into deionized water for ball milling and blending, evaporating the solvent, and high-pressure molding to obtain the xonotlite product.

[0066] In some embodiments, after performing vacuum impregnation in step S4, the modified calcium carbonate can be obtained by immersing in an ethanol aqueous solution with an ethanol volume fraction of 10-30% for 24-48 hours for aging. In fact, the aging treatment can be carried out at 2-3atm (standard atmospheric pressure), which is conducive to improving the aging effect of the calcium silicate composite. Specifically, after aging, vacuum drying is carried out to obtain the modified calcium silicate. In fact, the drying means used can be hot air drying, heating drying, supercritical drying and other commonly used means in the art.

[0067] In some embodiments, when executing step S5, the modified calcium silicate is put into a ball mill, at a ball-to-material ratio of (15-25):1, calcium oxide is used as the ball mill, and the ball mill is rotated at 100-200 rpm for 10-12 hours to obtain calcium silicate nanosheets.

[0068] In fact, the present invention also provides calcium silicate nanosheets obtained by exfoliation in any of the above optional embodiments. Example 1

[0069] This embodiment 1 provides a method for preparing calcium silicate nanosheets, comprising the following steps: S1. Preheat calcium silicate powder (calcium silicate powder with a mesh size of 3000 purchased from Shenzhen Guijing Industrial Co., Ltd.) in a vacuum environment at 50°C, and stir and mix γ-chloropropyltrimethoxysilane (CAS: 2530-87-2, the mass ratio of calcium silicate powder to γ-chloropropyltrimethoxysilane is 1:0.15) in anhydrous ethanol (the volume ratio of anhydrous ethanol to γ-chloropropyltrimethoxysilane is 2:1) to prepare a coupling solution. Then, heat the coupling solution at 50°C. After keeping warm in a water bath environment for 0.5 h, the preheated calcium silicate powder was put into the coupling solution and ultrasonically mixed at a frequency of 20 kHz for 10 min, and then the solid and the residual liquid were separated by vacuum filtration. The solid was rinsed three times with the residual liquid, and then the solid was mixed with deionized water at a mass ratio of 1:1, and then centrifuged and washed at a speed of 150 rpm in a centrifugal device, and the centrifugal precipitate was separated and dried in a vacuum drying oven at 60°C to constant weight to obtain activated calcium silicate; S2. Preheat the activated calcium silicate in a vacuum environment at 50°C, keep tetraethyl orthosilicate (CAS: 78-10-4, the mass ratio of activated calcium silicate to tetraethyl orthosilicate is 1:7) in a water bath at 50°C for 0.5h, add the preheated activated calcium silicate into the tetraethyl orthosilicate, add anhydrous ethanol to adjust the solid content of the activated calcium silicate in the suspension to 0.12 g / mL, and perform ultrasonic mixing at a frequency of 20kHz for 10min to obtain a mixed suspension; S3, pre-preparing a saturated calcium chloride aqueous solution, keeping the mixed suspension warm in a 45°C water bath, then dropping the saturated calcium chloride aqueous solution dropwise into the mixed suspension, applying an ultrasonic treatment at a frequency of 10 kHz to the outside of the mixed suspension, controlling the total dropping time of the saturated calcium chloride aqueous solution to be 45 min, and controlling the mass ratio of the total mass of the added calcium ions to the mass of the activated calcium silicate to be 0.03:1; after the dropping is completed, standing at 45°C and keeping warm for 5 hours, filtering and separating, and washing the obtained solid with deionized water to obtain a calcium silicate gel; S4, mixing calcium hydroxide, silicon dioxide and potassium hydroxide in a mass ratio of 10:10:0.1 into deionized water, and ball milling and blending in a ball mill at 300rpm to obtain a mixed slurry, evaporating the deionized water in the mixed slurry, and shaping at 1200°C and a pressure of 500kPa to obtain a hard asphaltite product; placing the hard asphaltite product in a vacuum device at 50pa in advance, adding a calcium silicate gel with a mass ratio of 1:0.4 to the hard asphaltite product into the vacuum device, and making the hard asphaltite product completely immersed in the calcium silicate gel, after immersing in the vacuum device for 4h, adding an ethanol aqueous solution with a volume fraction of 20% ethanol to completely immerse the hard asphaltite product, aging at a pressure of 2atm for 48h, and vacuum drying to obtain modified calcium silicate; S5. The modified calcium silicate is put into a ball mill, and calcium oxide is used as a ball mill at a ball-to-material ratio of 20:1. The ball mill is rotated at 150 rpm for 12 hours to obtain calcium silicate nanosheets.

[0070] Comparative Example 1 This comparative example 1 provides a method for preparing calcium silicate nanosheets, comprising the following steps: D1. Preheat calcium silicate powder (calcium silicate powder with a mesh size of 3000 purchased from Shenzhen Guijing Industrial Co., Ltd.) in a vacuum environment at 50°C, then keep tetraethyl orthosilicate (CAS: 78-10-4, the mass ratio of calcium silicate powder to tetraethyl orthosilicate is 1:7) in a 50°C water bath environment for 0.5h, add the preheated calcium silicate powder into tetraethyl orthosilicate, and add anhydrous ethanol to adjust the solid content of the calcium silicate powder in the suspension to 0.12 g / mL, and then perform ultrasonic mixing at a frequency of 20kHz for 10min to obtain a mixed suspension; D2. Pre-prepare a saturated calcium chloride aqueous solution, keep the mixed suspension warm in a 45°C water bath, then drop the saturated calcium chloride aqueous solution into the mixed suspension dropwise, apply ultrasonic treatment at a frequency of 10 kHz to the outside of the mixed suspension, control the total dripping time of the saturated calcium chloride aqueous solution to be 45 min, and control the total mass of the added calcium ions to the mass ratio of the activated calcium silicate to be 0.03:1; after the dripping is completed, stand at 45°C and keep warm for 5 hours, filter and separate, and use deionized water to rinse the obtained solid to obtain a calcium silicate gel; D3, calcium hydroxide, silicon dioxide and potassium hydroxide are mixed in a mass ratio of 10:10:0.1 and put into deionized water, and then ball-milled and blended in a ball mill at 300 rpm to obtain a mixed slurry, and the deionized water in the mixed slurry is evaporated and then molded at 1200°C and a pressure of 500 kPa to obtain a xonotlite product; the xonotlite product is pre-placed in a vacuum device at 50 pa, and a calcium silicate gel with a mass ratio of 1:0.4 to the xonotlite product is added into the vacuum device, and the xonotlite product is completely immersed in the calcium silicate gel, and after being immersed in the vacuum device for 4 hours, an ethanol aqueous solution with a volume fraction of 20% is added to completely immerse the xonotlite product, and after aging treatment at a pressure of 2 atm for 48 hours, vacuum drying is performed to obtain modified calcium silicate; D4. The modified calcium silicate was put into a ball mill at a ball-to-material ratio of 20:1, calcium oxide was used as the ball mill, and the ball mill was rotated at 150 rpm for 12 hours to obtain calcium silicate nanoparticles.

[0071] Performance Testing The calcium silicate nanosheets prepared in Example 1 and Comparative Example 1 were tested for stability. 10 g of calcium silicate nanosheets were ground and added with 20 mL of distilled water to prepare a suspension. The suspension was diluted 5 times and centrifuged at 60 rpm for 30 min to observe whether stratification and precipitation occurred, and the duration of stratification and precipitation was observed to evaluate its dispersion stability. The results are shown in Table 1 below.

[0072] Table 1 Stability test results

[0073] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for exfoliating calcium silicate nanosheets, characterized in that: The following steps are involved: The activated calcium silicate is prepared by mixing calcium silicate powder in a silicon-containing coupling agent, separating and drying the mixture, and ultrasonically mixing the activated calcium silicate with ethyl orthosilicate to prepare a mixed suspension. The mixed suspension is ultrasonically mixed with a calcium ion solution and separated to prepare a calcium silicate gel. The calcium silicate gel and a xonotlite product are vacuum impregnated and then aged to prepare modified calcium silicate. The modified calcium silicate is ball-milled and exfoliated to prepare calcium silicate nanosheets.

2. The stripping method according to claim 1, characterized in that: When the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the average particle size of the calcium silicate powder is 1-5 μm; and / or the volume density of the calcium silicate powder is 0.2-0.5 g / m 3 ; and / or, the mass ratio of the calcium silicate powder to the silicon-containing coupling agent is 1:(0.1-0.2); and / or, the silicon-containing coupling agent includes one of γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, phenyltriethoxysilane and dodecyltrimethoxysilane.

3. The stripping method according to claim 1, characterized in that: When the activated calcium silicate is obtained by separation and drying: after vacuum filtration, drying is performed to obtain the activated calcium silicate; and / or, after separation, drying is performed at 50-70° C. to obtain the activated calcium silicate; and / or, after separation, drying is performed under a vacuum environment to obtain the activated calcium silicate; and / or, after separation, washing is performed with a solution containing a silicon-containing coupling agent, and drying is performed to obtain the activated calcium silicate; and / or, after separation, centrifugal washing is performed with deionized water at 100-200 rpm, and drying is performed to obtain the activated calcium silicate.

4. The stripping method according to claim 1, characterized in that: When the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed to obtain a mixed suspension: the mass ratio of the activated calcium silicate to the ethyl orthosilicate is 1:(5-10); and / or, the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed at a frequency of 10-30 kHz; and / or, the mixed suspension is mixed with anhydrous ethanol and then adjusted to a solid content of the activated calcium silicate of 0.1-0.12 g / mL; and / or, the activated calcium silicate is preheated at 40-50° C. and then ultrasonically mixed with ethyl orthosilicate; and / or, the activated calcium silicate and ethyl orthosilicate are ultrasonically mixed at 40-50° C. to obtain a mixed suspension.

5. The stripping method according to claim 1, characterized in that: When the mixed suspension is ultrasonically mixed with the calcium ion solution: the calcium ion solute in the calcium ion solution includes one of calcium chloride, calcium nitrate and calcium acetate; and / or, the calcium ion solution is dropwise added to the mixed suspension under ultrasonic conditions for mixing; and / or, the mass ratio of activated calcium silicate in the mixed suspension to calcium ions in the calcium ion solution is 1:(0.02-0.04); and / or, the solvent of the calcium ion solution includes deionized water; and / or, the mixed suspension and the calcium ion solution are ultrasonically mixed at 40-50° C.; and / or, the mixed suspension and the calcium ion solution are ultrasonically mixed at a frequency of 10-30 kHz.

6. The stripping method according to claim 1, characterized in that: When the calcium silicate gel and the xonotlite product are vacuum impregnated: the mass ratio of the calcium silicate gel to the xonotlite product is 1:(0.3-0.5); and / or, the calcium silicate gel and the xonotlite product are impregnated in a vacuum environment for 2-4 hours; and / or, the xonotlite product is prepared from a calcium-containing raw material and a silicon-containing raw material in an alkaline environment; and / or, in a vacuum environment, the xonotlite product is immersed in the calcium silicate gel.

7. The stripping method according to claim 1, characterized in that: When the modified calcium silicate is obtained by aging after vacuum impregnation: after vacuum impregnation, the modified calcium silicate is obtained by immersing in an ethanol aqueous solution with an ethanol volume fraction of 10-30% for 24-48 hours for aging; and / or, after vacuum impregnation, the modified calcium silicate is obtained by aging under a pressure of 2-3atm; and / or, after vacuum impregnation and aging, the modified calcium silicate is obtained by vacuum drying.

8. The stripping method according to claim 1, characterized in that: When the modified calcium silicate is subjected to ball milling and exfoliation to obtain calcium silicate nanosheets, the modified calcium silicate is subjected to ball milling and exfoliation at a ball-to-material ratio of (15-25):1 at a rotation speed of 100-200 rpm for 10-12 hours to obtain the calcium silicate nanosheets.

9. The stripping method according to claim 1, characterized in that: When the calcium silicate powder is stirred and mixed in the silicon-containing coupling agent: the silicon-containing coupling agent is dissolved in advance to obtain a coupling solution, and then the calcium silicate powder is ultrasonically mixed in the coupling solution; and / or, the calcium silicate powder is kept warm in a vacuum environment at 50-55° C. for pre-activation; and / or, the calcium silicate powder and the silicon-containing coupling agent are stirred and mixed at 50-55° C.

10. A calcium silicate nanosheet obtained by exfoliation according to the exfoliation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano-structured silicate, functionalised forms thereof, preparation and uses

    CN101142140A

  • Preparation method of calcium silicate hydrate nano material

    CN103449460A

  • Calcium silicate nanocrystallization and nanosheet stripping method

    CN117361550A

  • Method for preparing calcium metasilicate nano material

    CN1554585A

  • Calcium silicate hydrate and its production

    JP1994128412A